2019
DOI: 10.24057/2071-9388-2019-72
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol and Its Radiative Effects during the Aeroradcity 2018 Moscow Experiment

Abstract: During the AeroRadCity-2018 spring aerosol experiment at the Moscow State University Meteorological Observatory the aerosol properties of the atmosphere and radiative aerosol effects were analyzed using a wide complex of measurements and model COSMO-ART simulations over Moscow domain. The program of measurements consisted of columnar aerosol AERONET retrievals, surface PM10, black carbon (BC) and aerosol gas precursors mass concentrations, as well as radiative measurements under various meteorological conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…The high values were simulated over industrial areas in Southern Poland: 1.8 µg m −3 in January and 1.0 µg m −3 in July, which is similar to the elemental carbon data in [50]. The black carbon concentration over the Moscow area was at its largest in March, amounting to about 1.6 µg m −3 , which is close to the values measured during the AeroRadCity-2018 spring aerosol experiment in Moscow [57]. These comparisons confirm the reliability of the GEOS-Chem evaluations of black carbon content.…”
Section: Discussionsupporting
confidence: 82%
“…The high values were simulated over industrial areas in Southern Poland: 1.8 µg m −3 in January and 1.0 µg m −3 in July, which is similar to the elemental carbon data in [50]. The black carbon concentration over the Moscow area was at its largest in March, amounting to about 1.6 µg m −3 , which is close to the values measured during the AeroRadCity-2018 spring aerosol experiment in Moscow [57]. These comparisons confirm the reliability of the GEOS-Chem evaluations of black carbon content.…”
Section: Discussionsupporting
confidence: 82%
“…This study can be extended by analysing the impact of air pollutants on atmospheric properties and human health in India (Chubarova et al 2019)…”
Section: Discussionmentioning
confidence: 99%
“…The study of the rainwater chemical composition was carried out in April-May 2018 at the MO MSU during the AeroRadCity experiment (Chubarova et al, 2019). The MO MSU is located in the southwestern part of the city at the territory of the MSU Botanical Garden, far from industrial sources of pollution and major highways; and therefore is considered as a background city station (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study of the solubility and partitioning of PTEs during spring rains in Moscow showed that anthropogenic sources contributed significantly to the concentration of soluble PTEs; for the insoluble PTEs, crustal materials were the important contributors (Vlasov et al 2021a). The spring period was chosen because of the largest variety of meteorological conditions, typical for both cold and warm seasons, and emissions of pollutants into the atmosphere from various sources that were previously observed during spring months (Chubarova et al 2019;Elansky et al 2020;Popovicheva et al 2020a). However, studies of the intensity of soluble PTEs washout from the atmosphere by rains within the city have not been previously conducted.…”
Section: Introductionmentioning
confidence: 99%